Aggressiveness and host specificity of Brazilian isolates of Phytophthora infestans - Suassuna, N. D.; Maffia, L. A.; Mizubuti, E. S. G. (Plant Pathology, 2004)
The population of Phytophthora infestans in Brazil consists of two clonal lineages, US-1 associated with tomatoes and BR-1 associated with potatoes. To assess whether host specificity in these lineages resulted from differences in aggres- siveness to potato and tomato, six aggressiveness-related epidemiological components – infection frequency (IF), incu- bation period (IP), latent period (LP), lesion area (LA), lesion expansion rate (LER) and sporulation at several lesion ages (SSLA) – were measured on detached leaflets of late blight-susceptible potato and tomato plants. Infection frequency of US-1 was similar on potato and tomato leaflets, but IF of BR-1 was somewhat reduced on tomato. Incubation period was longer on both hosts with US-1, although this apparent lineage affect was not significant. Overall there was no host effect on IP. On potato, BR-1 had a shorter LP (110·3 h) and a larger LA (6·5 cm 2 ) than US-1 (LP = 162·0 h; LA = 2·8 cm 2 ). The highest LER resulted when isolates of BR-1 (0·121 cm 2 h −1 ) and US-1 (0·053 cm 2 h −1 ) were inoculated on potato and tomato leaflets, respectively. The highest values of the area under the sporulation capacity curve (AUSC) were obtained for isolates of US-1 inoculated on tomato leaflets (6146) and for isolates of BR-1 on potato leaflets (3775). In general, higher values of LA, LER, SSLA and AUSC, and shorter values of LP were measured when isolates of a clonal lineage were inoculated on their original host than with the opposite combinations. There is evidence that there are quan- titative differences in aggressiveness components between isolates of US-1 and BR-1 clonal lineages that probably con- tribute to host specificity of P. infestans populations in Brazil.
Keywords: Epidemiology; Late blight; Potato; Solanum lycopersicum; Solanum tuberosum; Tomato